The socio-economic burden of cystic echinococcosis in Morocco: A combination of estimation method. - Aouatif Saadi; Fatimaezzahra Amarir; Hind Filali; Séverine Thys; Abdelkbir Rhalem; Nathalie Kirschvink; Marianne Raes; Tanguy Marcotty; Mohamed Oukessou; Luc Duchateau; Hamid Sahibi; Nicolas Antoine-Moussiaux (Public Library of Science (PLoS), 2020)
Cystic echinococcosis (CE) is a major zoonosis in Morocco despite the launch of a national control programme in 2005. As its economic consequences have not been studied yet in Morocco, this study estimated CE impact in terms of monetary losses, disability-adjusted life years (DALY), and DALY for zoonotic diseases (zDALY) in the entire country and in specific regions for the 2011 to 2014 period. The direct monetary losses were related to organ seizure from infected animal in slaughterhouses, and to healthcare expenses as well as lost wages for infected humans. Animal production losses concerned milk yield, fertility, carcass weight, and wool production. Losses due to human infection were also composed of disability and productivity losses at work. Monte Carlo simulations were used to estimate monetary losses and zDALY values. Nationwide, the estimated DALY was 0.5 years per 100,000 persons per year, and the zDALY was 55 years per 100,000 persons per year. Total yearly losses were estimated at 73 million USD (54-92 million USD). However, losses differed significantly among regions. Most of the economic losses consisted of unperceived consequences, i.e. decreased animal production and reduced productivity of asymptomatic individuals. Future studies should determine the socioeconomic and epidemiological factors underlying the differences in economic losses among regions to develop better adapted control programmes.